Synthesis of Fe3O4-PVP nanocomposite functionalized with sulfonic group as an effective catalyst for one-pot synthesis of xanthene derivatives - Karegar, Mohsen; Khodaei, Mohammad Mehdi (Research on chemical intermediates, 2021)
An effective and environmentally friendly Fe 3 O 4 -PVP nanocomposite functionalized with sulfonic group, Fe 3 O 4 -PVP-SO 3 H, was synthesized and characterized as the heterogeneous nanocatalyst for one-pot synthesis of xanthene derivatives via condensation reaction of various aldehydes and dimedone in ethanol media. The catalyst was efficient, and can be separated easily from the reaction mixture and recovered rapidly by an external magnetic field. It can be used five times without significant loss of its activity. Physicochemical properties were characterized using different techniques including FT-IR, XRD, FE-SEM, EDS, TGA, and VSM to illustrate the structure of the catalyst. The presence of sulfonic group on the surface of the catalyst was confirmed by these analyses. Large number of the acidic groups on the surface of the PVP layer led to the more activity of the catalyst and consequently, the yield of xanthene increases. The products were obtained in high yields with short reaction times.